Лексикографічна репрезентація гіперонімо-гіпонімічних зв’язків (на матеріалі дефініцій зоонімів - Шевчук, Анна Володимирівна; Shevchuk, A. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено проблемі вираження гіперонімо-гіпонімічних зв’язків у дефініціях зоонімів, вибраних із трьох тлумачних словників сучасної англійської мови. Основним способом репрезентації цих зв’язків є родо-видовий тип тлумачення через найближчий гіперонім з вказівкою на видові відмінності. Показано, що в лексикографічній практиці загальної схеми тлумачення лексем-зоонімів часто не дотримуються і тому вона потребує уніфікації. The article deals with the expression of hypernym and hyponym relations in definitions of lexemes-animal names, selected from three dictionaries of contemporary English. The genus-species type of interpretation is used to represent this kind of relations. The paper considers the various modification options regarding definitions being under investigation. It is stated that very often in lexicographical practice the general interpretation scheme of lexemes animal names is violated. Consequently some unification concerning dictionary explanations of the elements of the definite hyponymic group is required.
Lexicographic representation hypernym and hyponym relations (based on entries of lexemes-animal names
Keywords: гіперонім; hypernym; гіпонім; hyponym; зоонім; animal name